Smart Home Remote Control System Prototype Using Internet of Things (IoT) Based ESP8266 Microcontroller - Adi Winarno; Widodo; Mochamad Kevin Nurcahyo (BEST, 2023)
Technology is developing very rapidly in the current era, there will be several impacts that will result from the development of technology. Electronic equipment control can be done remotely in real time using the IoT system. The problem faced is the concern when leaving home. Because when leaving the house, homeowners sometimes often forget about electronic devices whether they are turned off or still on. IoT can be utilized at home as a smart home system by connecting an electronic device to an android application. This IoT-based smart home system uses an ESP8266 microcontroller which is used to connect between hardware and software that is controlled through the Blynk application. Blynk application is used as an interface that functions to provide input and produce output. This system consists of four sensors, namely the MQ2 sensor to detect gas leaks in the kitchen, the DHT11 sensor to determine the level of humidity and temperature in the bedroom, the PIR sensor to detect human movement at the front entrance, the ULTRASONIC sensor as a detector of the water level in the water reservoir and using three relays as a connector for lights and other electronic components. And using the Blynk application as a control system on the ESP8266 microcontroller.